2018
DOI: 10.3390/en11051214
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Assisted Pelleting of Sorghum Stalk: Predictive Models for Pellet Density and Durability Using Multiple Response Surface Methodology

Abstract: In the field of renewable energy, feedstock such as cellulosic biomass has been proposed as a renewable source of fuel to produce energy. However, the use of raw biomass as feedstock causes high costs in handling, transportation, and storage. Compressing raw cellulosic biomass into pellets significantly increases the density and durability of cellulosic biomass, reducing the transportation and handling costs of feedstock. To ensure high pellet quality, high pellet density and durability are desired during a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…In recent years, some novel pellets made from different biomass residues such as beech sawdust [11], Scenedesmus microalgae [12], canola hull mixed meal [6], corncobs [13,14], wheat straw [15], and coir fibers [16] have been investigated, and those studies focused on how the characteristics and quality of the pellets (bulk density, mechanical durability, energy consumption, and net calorific value [17,18]) can be influenced by various factors related to the raw material (chemical composition, moisture content [16], and production process (pressure, temperature [14]). Response surface methodology (RSM) is one of the most popular methods for parameter optimization of pelletization and has been extensively studied [19,20]. RSM is a mathematical modeling tool for predicting the output relationship under multiple input parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, some novel pellets made from different biomass residues such as beech sawdust [11], Scenedesmus microalgae [12], canola hull mixed meal [6], corncobs [13,14], wheat straw [15], and coir fibers [16] have been investigated, and those studies focused on how the characteristics and quality of the pellets (bulk density, mechanical durability, energy consumption, and net calorific value [17,18]) can be influenced by various factors related to the raw material (chemical composition, moisture content [16], and production process (pressure, temperature [14]). Response surface methodology (RSM) is one of the most popular methods for parameter optimization of pelletization and has been extensively studied [19,20]. RSM is a mathematical modeling tool for predicting the output relationship under multiple input parameters.…”
Section: Introductionmentioning
confidence: 99%
“…RSM is a mathematical modeling tool for predicting the output relationship under multiple input parameters. It is an optimization method widely used in the engineering field that provides an approximation technique for optimizing the problem and other subroutines [19]. RSM provides a function called the response surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the context of carbon peak and carbon neutrality, the increasing demand for low-cost, clean, and renewable energy necessitates a comprehensive utilization of agricultural residues, which are associated with high costs in handling, transportation, and storage [5]. Pelleting, a process that compresses biomass into uniform pellets of consistent shape and size, has been shown to significantly increase the density of cellulosic biomass [6][7][8]. The solid density of biomass could reach 1200 kg/m 3 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Song et al (2015) showed that the pelleting density would increase with the increase of the ultrasonic power in the ultrasonic-assisted pelleting process. Zhang et al (2018) put forward predictive models for pellet density and durability in ultrasonic vibration-assisted pelleting using multiple response surface methodology. In order to reduce energy consumption, Song et al (2013Song et al ( , 2014 studied the effect of sieve size, pelleting pressure, ultrasonic power, and pellet weight on energy consumption, and proposed a predictive model for energy consumption in ultrasonic vibration-assisted pelleting of wheat straw using response surface methodology.…”
Section: Introductionmentioning
confidence: 99%